Hoverbike / Nabilah Naharudin, Nursyafika Sahrin … [et al.] - NAHARUDIN, NABILAH; SAHRIN, NURSYAFIKA; MOHD ASRI, NUR ALIAH ADILLA; BUNIRAN, NOR SHAFIKA; ABD AZIZ, MOHD QAEDI FAIZ (2018)
Hover board is a self-balancing personal transportation consist of two motorized wheels connected to a controller pad where rider place their feet. Recently certain country have banned these hoverboard due to lack of safety. Many cases have been reported that an accident occur due to imbalance of using the hover board. Parents were advised to not to buy these hover board for children under 14 years old age. Therefore, the team decided to innovate the hoverboard become hoverbike. Hover bike is easy to ride and more stable compared to normal hover board. It consists of three tire which is more stable and have a compressible seat for rider to rest instead of standing in a long time. With hover bike, parents won't be worrying anymore about their children on falling from the hoverboard.